Research methods for communication science - Watt, James H.; Berg, Sjef A. van den
A textbook for communications students that integrates the basic rules of science with the research procedures that follow those rules. Suitable for undergraduates and as a first research methods text for graduate students. This book integrates the basic philosophy of science, statistics, research design, and investigatory procedures in order to tell the reader why they are conducting research using the described methods and how to do them. Both the quantitative and qualitative methods of research are defined.